MaNGA galaxy properties – I. An extensive optical, mid-infrared photometric, and environmental catalogue. Issue 3 (19th May 2021) - Arora, Nikhil; Stone, Connor; Courteau, Stéphane; Jarrett, Thomas H
ABSTRACT: We present an extensive catalogue of non-parametric structural properties derived from optical and mid-infrared imaging for 4585 galaxies from the MaNGA survey. DESI and Wide-field Infrared Survey Explorer ( WISE ) imaging are used to extract surface brightness profiles in the g, r, z, W 1, W 2 photometric bands. Our optical photometry takes advantage of the automated algorithm autoprof and probes surface brightnesses that typically reach below 29 mag arcsec −2 in the r -band, while our WISE photometry achieves 28 mag arcsec −2 in the W 1-band. Neighbour density measures and central/satellite classifications are also provided for a large subsample of the MaNGA galaxies. Highlights of our analysis of galaxy light profiles include (i) an extensive comparison of galaxian structural properties that illustrates the robustness of non-parametric extraction of light profiles over parametric methods; (ii) the ubiquity of bimodal structural properties, suggesting the existence of galaxy families in multiple dimensions; and (iii) an appreciation that structural properties measured relative to total light, regardless of the fractional levels, are uncertain. We study galaxy scaling relations based on photometric parameters, and present detailed comparisons with literature and theory. Salient features of this analysis include the near-constancy of the slope and scatter of the size–luminosity and size–stellar mass relations for late-type galaxies with wavelength, and the saturation of central surface density, measured within 1 kpc, for elliptical galaxies with $M_* \gt 10.7\, {\rm M}_{\odot }$ (corresponding to $Σ _1 \simeq 10^{10}\, {\rm M}_{\odot }\, {\rm kpc}^{-2}$ ). The multiband photometry, environmental parameters, and structural scaling relations presented are useful constraints for stellar population and galaxy formation models.